2020
DOI: 10.1007/s10549-020-05705-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors of complications in different breast reconstruction methods

Abstract: Purpose Women with different BMI, age and comorbidities seek for breast reconstruction. It is critical to understand the risk associated with each technique to ensure the most appropriate method and timing is used. Outcome after reconstructions have been studied, but consensus is lacking regarding predictive risk factors of complications. The authors present their experience of different autologous and alloplastic reconstructions with an emphasis on predictors of complications. Methods Prospectively maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
(55 reference statements)
1
27
0
Order By: Relevance
“…First, Chang et al observed significantly higher rates of complications in overweight and obese patients having a breast reconstruction with free TRAM flaps [ 1 ]. Besides higher frequencies of lower abdominal bulging and herniation due to increased intraabdominal pressure in overweight patients [ 17 , 18 ], several studies confirmed a significantly higher overall risk for complications after reconstructions with abdominal based free flaps [ 3 , 4 , 19 , 20 , 21 , 22 , 23 ]. As an example, Boczar et al [ 4 ] observed a reoperation rate of about 40% in obese patients and severe wound complications.…”
Section: Discussionmentioning
confidence: 99%
“…First, Chang et al observed significantly higher rates of complications in overweight and obese patients having a breast reconstruction with free TRAM flaps [ 1 ]. Besides higher frequencies of lower abdominal bulging and herniation due to increased intraabdominal pressure in overweight patients [ 17 , 18 ], several studies confirmed a significantly higher overall risk for complications after reconstructions with abdominal based free flaps [ 3 , 4 , 19 , 20 , 21 , 22 , 23 ]. As an example, Boczar et al [ 4 ] observed a reoperation rate of about 40% in obese patients and severe wound complications.…”
Section: Discussionmentioning
confidence: 99%
“…Six NRCSs reported risks of overall (or "any") complications. Seven of these NRCSs (Chetta 2017, Kouwenberg 2020, Kulkarni 2017, Mak 2020, Palve 2020, Qin 2018, and Simon 2020), reported that, between 1 month and 3.7 years of followup, risks were higher among patients who underwent AR than those who underwent IBR (adjORs ranged from 1.36 to 8.28). Kulkarni 2017 reported separate comparisons between various AR flap types and IBR; risks of overall complications were higher for each flap group (DIEP, free TRAM, pedicled TRAM, LD, and SIEA) than the IBR group at both 1 and 2 years.…”
Section: Composite or Unspecified Harmsmentioning
confidence: 99%
“…More specifically, while prepectoral implant placement is a promising technique, appropriate patient selection is crucial. Evolution in NSM techniques, emphasis on intraoperative skin flap assessment, assessment of patients’ skin flap thickness and vascularity, have led to improved skin flap viability, which has reintroduced the prepectoral prosthetic breast reconstruction approach [33-36].…”
Section: Autologous Versus Alloplastic Breast Reconstruction (Prepectoral Vs Subpectoral Approach) – Complicationsmentioning
confidence: 99%